Critical Studies of the Arctic
XII, 283 p. 2 illus., 1 illus. in color.
Keywords: This book is a pioneering effort in critical Arctic studies. The contributions identify and investigate some of the blind spots in human development in the Arctic that research in the social sciences had yet to broach. To this end, the authors tap a variety of critical approaches in fields spanning aesthetics, affect theory, biopolitics, critical geopolitics, Indigenous archaeology, intersectionality, legal anthropology, moral economy, narrative studies, neoliberal governmentality, queer studies and socio-legal studies. The chapters probe topics such as representations of the Arctic in contemporary art, the role of affects in postcolonial Greenland, Canada’s Arctic policies and China’s engagement with the Arctic. The book provides a rich knowledge base for researchers in Arctic social sciences and offers an absorbing textbook for students interested in Arctic issues. Marjo Lindroth is Researcher in the Arctic Centre at the University of Lapland, Finland. Her research critically investigates the intersections between power, rights and indigeneity in international politics. Heidi Sinevaara-Niskanen is Researcher in Gender Studies at the University of Lapland, Finland. Her critical research addresses the problematics of development, power and social sustainability, with particular reference to Arctic politics. Monica Tennberg is Research Professor at the Arctic Centre, University of Lapland, Finland, where she leads the Northern Political Economy research group and coordinates the UArctic thematic network on Critical Arctic Studies (CAS).